Analisis Bentuk Frasa pada Kumpulan Cerpen Surat yang Dikirim Lewat Angin Karya Hari B. Mardikantoro: Analysis of the form of phrases in a collection of short stories “Surat yang Dikirim Lewat Angin” by Hari B. Mardikantoro - Lailatunnihayah, Lailatunnihayah; Hasanudin, Cahyo; Rohman, Nur (Himpunan Sarjana Kesusastraan Indonesia (HISKI) Komisariat Kalimantan Timur, 2023)
This study aims to describe the forms of endocentric and exocentric phrases in a collection of short stories of Surat yang Dikirim Lewat Angin by Hari B. Mardikantoro. This study used descriptive qualitative method. The technique of collecting data in this study is the technique of listening freely, speaking and taking notes. The results of this study indicate that there are forms of coordinating phrases, attributive phrases, and apositive phrases as well as exocentric directive and non-directive phrase forms in Hari B. Mardikantoro's short story collection of Surat yang Dikirim Lewat Angin.